Chemical burns to scalp from hair bleach: a retrospective case series - Omar Noori; Peter Maitz; Jeon Cha; Andrea C Issler-Fisher (Australasian Journal of Plastic Surgery)
**Background:** Hair bleaching has become a common cosmetic procedure and the use of cytotoxic chemicals can cause serious burns to the skin.